Effect of smoking on status of hearing: A cross-sectional study - Nandita Gautam; Shivalingesh KK; Anushtha Kushwaha; Varnika Singh; Siddhant Singh; Shashank Kumar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2022)
Introduction: Smoking is a common tendency among all social classes around the globe, especially in the working population.  Objective: To assess the significant link between tobacco and cigarette smoking and its effect on hearing among smokers as there is limited study on this aspect of the Indian population particularly with a high-frequency hearing threshold.  Methodology: Cross-sectional study carried out on patients attending the OPD in ENT and Head & Neck Surgery Department of Rohilkhand Medical College & Hospital. The sample size came to be 90.  Results: In smokers, there were 72 (80%) males and 18 (20%) females while in the non-smoker group, there were 53 (58.8%) males and 37 (41.11%) females, and 39 (43.3%) subjects belonging to the rural population while 51 (56.7%) subjects belong to an urban population. out of 90 subjects, 43 (30.3%) had cochlear deafness followed by 40 (28.2%) who had normal hearing and 7 (4.9%) had retrocochlear deafness.  Conclusion: Tobacco has the power to reduce the ability to hear, mainly causing a sensorineural hearing loss at higher frequencies.